International Comparisons of Bulgaria’s Health System Performance - World Bank (World Bank, Washington, DC, 2015)
Relative to other comparable income and health spending countries, Bulgaria has more physicians per capita. Bulgaria’s physician to population ratio increased from 2.5 in 1980 to 3.8 physicians per 1000 population in 2011. The physician to population ratio is comparable to the EU-12 average of 3.8 physicians per 1000 population in 2012 but is higher than the EU-15 average of 3.1 physicians per 1000 population in 2012. Bulgaria has achieved significant improvements in health outcomes over time but is still falling behind most EU countries on key health indicators. Infant mortality decreased from 24.5 in 1980 to 10.5 per 1,000 live births in 2012 (Figure 5). Infant mortality in Bulgaria is slightly lower relative to other comparable income and health spending countries. Despite the significant reduction, however, Bulgaria’s infant mortality rate is still more than three times higher than the EU-15 average of 3.2 infant deaths per 1000 live births and almost twice as high as the EU-12 average of 5.5 infant deaths per 1000 live births. More significant improvements were achieved in reducing maternal mortality, which fell from 24 deaths per 100,000 live births in 1990 to 8 deaths per 100,000 live births in 2010. The maternal mortality ratio in Bulgaria is low compared to the global averages relative to income and health spending. Bulgaria has surpassed the EU-12 average of 11.3 deaths per 100,000 live births and is approaching the EU-15 average of 7.6 deaths per 100,000 live births.